2005
DOI: 10.1091/mbc.e04-06-0459
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D Is Involved in Myogenic Differentiation through Remodeling of Actin Cytoskeleton

Abstract: We investigated the role of phospholipase D (PLD) and its product phosphatidic acid (PA) in myogenic differentiation of cultured L6 rat skeletal myoblasts. Arginine-vasopressin (AVP), a differentiation inducer, rapidly activated PLD in a Rho-dependent way, as shown by almost total suppression of activation by C3 exotoxin pretreatment. Addition of 1-butanol, which selectively inhibits PA production by PLD, markedly decreased AVP-induced myogenesis. Conversely, myogenesis was potentiated by PLD1b isoform overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 61 publications
8
72
1
Order By: Relevance
“…Several lines of evidence support our hypothesis. First, RhoA can interact with PLD1 when they are coexpressed in N2a cells, which is consistent with previous studies Bae et al, 1998;Yamazaki et al, 1999, Du et al, 2000Komati et al, 2005;Yoon et al, 2005;Gayral et al, 2006). Second, the reduction of dendritic branching caused by active RhoA can be partially rescued by PLD1 siRNA.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Several lines of evidence support our hypothesis. First, RhoA can interact with PLD1 when they are coexpressed in N2a cells, which is consistent with previous studies Bae et al, 1998;Yamazaki et al, 1999, Du et al, 2000Komati et al, 2005;Yoon et al, 2005;Gayral et al, 2006). Second, the reduction of dendritic branching caused by active RhoA can be partially rescued by PLD1 siRNA.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have suggested that RhoA directly interacts with and activates PLD1 both in vitro and in vivo Bae et al, 1998;Yamazaki et al, 1999;Du et al, 2000;Komati et al, 2005;Yoon et al, 2005;Gayral et al, 2006). In this study, we showed that PLD1 has the same effects as RhoA in reducing the number of dendritic branches.…”
Section: Pld1 Acts As Downstream Target Of Rhoa To Suppress Dendriticsupporting
confidence: 64%
See 1 more Smart Citation
“…C2C12 differentiation is markedly inhibited by 1-butanol, an inhibitor of the PLD-catalyzed transphosphatidylation reaction, and also by the knockdown of PLD1, but not PLD2. Further cytoskeleton (Komati et al, 2005). Notably, a potential role of PLD in the autocrine regulation of satellite cell differentiation upon growth factor withdrawal has not been examined, and whether, and how, PLD is involved in mTOR signaling in myogenic differentiation is not known.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that PLD interacts directly with the actin cytoskeleton. Komati et al (39) showed that PLD regulates myogenesis by inducing PA-dependent actin fiber formation. Roach et al (34) showed that PA regulates actin cytoskeletal reorganization by controlling the localization and function of PIPKI, an enzyme that produces the key actin cytoskeleton-regulating lipid, PI(4,5)P2.…”
Section: Discussionmentioning
confidence: 99%